ByzRev 02.2020.012: Tsvetelin Stepanov, Waiting for the End of the World. European Dimensions, 950–1200, translated by Daria Manova: (East Central and Eastern Europe in the Middle Ages, 450–1450, 57). Leiden – Boston: Brill 2019. - Kraft, András (The Byzantine Review, 2020)
Tsvetelin Stepanov, Waiting for the End of the World. European Dimensions, 950–1200, translated by Daria Manova (East Central and Eastern Europe in the Middle Ages, 450–1450, 57). Leiden – Boston: Brill 2019. Leiden – Boston: Brill 2019. 364 + xviii pp. – ISBN: 978-90-04-34393-1.